EFFECTS OF SIMULATED LABORATORY AND ENRICHED LABORATORY GUIDE MATERIAL EXPERIMENTS ON STUDENTS’ LEARNING OUTCOMES IN BASIC SCIENCE IN OYO STATE, NIGERIA (2017)
Basic Science is a core subject at the basic education level in Nigeria. It is taught to lay foundation for future subjects, such as Biology, Chemistry and Physics. Evidence abound that students dislike, fear and therefore fail the senior secondary science subjects due to inadequate exposure to practical works and skills at the basic education level. Previous studies largely focused on factors affecting teaching and learning of Basic Science practical without emphasis on intervention through regular conduct of laboratory experiments in the subject. This study, therefore, determined the effects of Simulated Laboratory (SL) and Enriched Laboratory Guide Material (ELGM) experiments on students’ achievement and acquisition of Science Process Skills (SPS) in Basic Science in Oyo State, Nigeria. The moderating effects of gender and future career interest in science were also examined. Bruner’s constructivist and Kolb’s experiential learning theories provided the framework, while the pretest-posttest control group quasi-experimental design with a 3x2x2 factorial matrix was adopted. Three local government areas were randomly selected from each of Ibadan (Ibadan South-East, Ibadan South-West, Ibadan North) and Oyo (Afijio, Oyo-East, Oyo-West). Six co-educational public secondary schools were purposively selected based on availability of functional computer and science laboratories. Six randomly selected intact classes of junior secondary three students (130 males and 147 females, ±17 years) were randomly assigned to SL (110), ELGM (60) and Conventional (Expository) Laboratory - CEL (107). The instruments used were: Achievement test in Basic Science (r=0.87), Science process skills test in Basic Science (r=0.72) and Future career interest in Science questionnaire (r=0.99). The treatments lasted seven weeks. Data were analysed using Analysis of covariance and Scheffé post-hoc test at 0.05 level of significance. Treatments had significant main effect (F(2,264)=25.88; partial η2=.16) on students’ achievement in Basic Science. Participants in the ELGM group had highest achievement mean score (24.91) followed by CEL (24.77) and SL (19.40). Future career interest in science had significant main effect (F(1,264)=4.08; partial η2=.02) on students’ achievement in Basic Science. Participants in the Science-Related (SR) group had higher achievement mean score (23.87) than Non-Science Related (NSR) group (22.18). Treatments had significant main effect (F(2,264)=25.51; partial η2=.16) on students’ acquisition of SPS in Basic Science. Participants in the SL group had highest SPS mean score (15.00) followed by ELGM (14.66) and CEL (12.59). Future career interest in science had significant main effect (F(1,264)=17.62; partial η2=.06) on students’ acquisition of SPS in Basic Science. Participants in the SR group had higher SPS acquisition mean score (14.81) than NSR (13.36). There was no significant main effect of gender on students’ achievement and acquisition of SPS in Basic Science. There were no significant two-way and three-way interaction effects on students’ achievement and acquisition of SPS in Basic Science. Enriched laboratory guide material experiment was more effective in enhancing achievement while Simulated laboratory experiment was more effective on acquisition of science process skills. The two modes of laboratory experiments should be adopted for improved achievement and acquisition of science process skills in Basic Science